Comparative gene expression profiling of human metallothionein-3 up-regulation in neuroblastoma cells and its impact on susceptibility to cisplatin - Merlos Rodrigo, Miguel Angel; Dostalova, Simona; Buchtelova, Hana; Strmiska, Vladislav; Michalek, Petr; Krizkova, Sona; Vicha, Ales; Jencova, Pavla; Eckschlager, Tomas; Stiborova, Marie; Heger, Zbynek; Adam, Vojtech (Oncotarget, 2018)
Human metallothionein-3 (hMT-3), also known as growth inhibitory factor, is predominantly expressed in the central nervous system. hMT-3 is presumed to participate in the processes of heavy metal detoxification, regulation of metabolism and protection against oxidative damage of free radicals in the central nervous system; thus, it could play important neuromodulatory and neuroprotective roles. However, the primary functions of hMT-3 and the mechanism underlying its multiple functions in neuroblastoma have not been elucidated so far. First, we confirmed relatively high expression of hMT-3 encoding mRNA in biopsies (n = 23) from high-risk neuroblastoma subjects. Therefore, we focused on investigation of the impact of hMT-3 up-regulation in N-Myc amplifying neuroblastoma cells. The differentially up-regulated genes involved in biological pathways related to cellular senescence and cell cycle were identified using electrochemical microarray with consequent bioinformatic processing. Further, as experimental verification of microarray data, the cytotoxicity of the cisplatin (CDDP) was examined in hMT-3 and mock cells by MTT and clonogenic assays. Overall, our data strongly suggest that up-regulation of hMT-3 positively correlates with the genes involved in oncogene-induced senescence (CDKN2B and ANAPC5) or apoptosis (CASP4). Moreover, we identified a significant increase in chemoresistance to cisplatin (CDDP) due to hMT-3 up-regulation (24IC50: 7.5 vs. 19.8 μg/ml), indicating its multipurpose biological significance.
Keywords: cisplatin; oncogene-induced senescence; chemoresistance; metallothionein; apoptosis